Illness Severity and Outcomes Among Enteric Fever Cases From Bangladesh, Nepal, and Pakistan: Data From the Surveillance for Enteric Fever in Asia Project, 2016–2019. (1st December 2020) - Longley, Ashley T; Hemlock, Caitlin; Date, Kashmira; Luby, Stephen P; Andrews, Jason R; Saha, Samir K; Bogoch, Isaac I; Yousafzai, Mohammad T; Garrett, Denise O; Qamar, Farah N
Abstract: Background: Enteric fever can lead to prolonged hospital stays, clinical complications, and death. The Surveillance for Enteric Fever in Asia Project (SEAP), a prospective surveillance study, characterized the burden of enteric fever, including illness severity, in selected settings in Bangladesh, Nepal, and Pakistan. We assessed disease severity, including hospitalization, clinical complications, and death among SEAP participants. Methods: We analyzed clinical and laboratory data from blood culture–confirmed enteric fever cases enrolled in SEAP hospitals and associated network laboratories from September 2016 to September 2019. We used hospitalization and duration of hospital stay as proxies for severity. We conducted a follow-up interview 6 weeks after enrollment to ascertain final outcomes. Results: Of the 8705 blood culture-confirmed enteric fever cases enrolled, we identified 6 deaths (case-fatality ratio, .07%; 95% CI, .01–.13%), 2 from Nepal, 4 from Pakistan, and none from Bangladesh. Overall, 1.7% (90/5205) of patients recruited from SEAP hospitals experienced a clinical complication (Bangladesh, 0.6% [18/3032]; Nepal, 2.3% [12/531]; Pakistan, 3.7% [60/1642]). The most identified complications were hepatitis (n = 36), septic shock (n = 22), and pulmonary complications/pneumonia (n = 13). Across countries, 32% (2804/8669) of patients with hospitalization data available were hospitalized (Bangladesh, 27% [1295/4868]; Nepal, 29% [455/1595]; Pakistan, 48% [1054/2206]), with a median hospital stay of 5 days (IQR, 3–7). Conclusions: While defined clinical complications and deaths were uncommon at the SEAP sites, the high proportion of hospitalizations and prolonged hospital stays highlight illness severity and the need for enteric fever control measures, including the use of typhoid conjugate vaccines.